Agreement on underlying causes of infant death between original records and after investigation: analysis of two biennia in the years 2000 - Hellen Geremias dos Santos; Selma Maffei de Andrade; Ana Maria Rigo Silva; Wladithe Organ de Carvalho; Arthur Eumann Mesas; Alberto Durán González (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
Objective: To analyze the agreement between underlying causes of infant deaths obtained from Death Certificates (DC) with those defined after investigation by the Municipal Committee for the Prevention of Maternal and Infant Mortality (CMPMMI), in Londrina, Paraná State, in the biennia 2000-2001 and 2007-2008. Methods: DC of infants and records of investigations were obtained from the CMPMMI. The causes of death registered in both sources were coded according to the International Classification of Diseases, tenth revision (ICD-10), and the underlying causes of deaths were selected. Agreement between underlying causes of deaths was verified by Kappa's (k) test and analyzed according to ICD-10 chapters and blocks of categories in both biennia. Results: In 2000/2001, according to ICD-10 chapters, high agreement rates were observed for conditions originated in the perinatal period (k = 0.85) and for external causes (k = 0.84), while, for congenital malformations, there was a substantial agreement (k = 0.71). In 2007/2008, agreement was considered poor for all analyzed chapters. For blocks of categories, high or substantial agreement rates were observed only in the first biennium for "congenital malformations of the circulatory system" (k = 0.78) and for "other external causes of accidental injury" (k = 0.91). Conclusions: A decrease in agreement between the sources during the study period indicates either an improvement in the process of investigation of infant death by the CMPMMI and/or a worsening in the quality of the DC information.